2006
DOI: 10.1016/j.psychres.2005.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Antecedent life events of binge-eating disorder

Abstract: The present study investigated the occurrence of life events preceding the onset of disturbed eating in binge-eating disorder (BED). In a case-control design, 162 matched pairs of black and white women with BED and women with no current psychiatric disorder, and 107 matched pairs of women with BED and a current general psychiatric disorder were recruited from the community for the New England Women's Health Project. Life events in the year before the onset of disturbed eating were assessed retrospectively with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
68
2
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(85 citation statements)
references
References 33 publications
9
68
2
6
Order By: Relevance
“…The most recalled shame experiences were experiences related to negative comments or criticism about body weight, shape and physical appearance, which is consistent with prior evidence that early weight and body image teasing experiences are an important factor involved in the etiology of BED (Fairburn et al, 1998;Jackson et al, 2000;Pike et al, 2006).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The most recalled shame experiences were experiences related to negative comments or criticism about body weight, shape and physical appearance, which is consistent with prior evidence that early weight and body image teasing experiences are an important factor involved in the etiology of BED (Fairburn et al, 1998;Jackson et al, 2000;Pike et al, 2006).…”
Section: Discussionsupporting
confidence: 83%
“…There is evidence that early negative experiences are a risk factor for BED (Caslini et al, 2016;Jackson et al, 2000;Pike et al, 2006;). Fairburn et al (1998) found that women with BED revealed greater exposure to adverse childhood experiences (e.g., parental criticism, peer bullying, sexual or physical abuse, critical comments about weight, shape or 4 eating) than women without eating disorders or with other psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Diversos autores plantean que el perfeccionismo constituye un rasgo psicológico fundamental en los TCA [29][30][31][32][33][34] , y es considerado como un factor de riesgo principal para su presentación [35][36][37] . La relación de TCA con estrés (OR = 0,993) y con el rasgo perfeccionismo (OR = 0,822) observadas en nuestro análisis, como factores de riesgo para desarrollar esta patología, concuerda con lo descrito por los expertos [27][28][29][30] , que plantean que el estrés sería un gatillante de conductas alimentarias alteradas en sujetos con ciertos rasgos premórbidos, aunque nuestros OR son más bajos que los de Pike et al 6 , que describen que la exposición a un mayor número de eventos vitales se asocia con seis veces mayor riesgo de desarrollar un TCA (3 o más eventos: OR = 5,8), mientras que la exposición a un menor número de eventos indicaba un riesgo menor (OR < 1,0). La prueba EAT-40 es un predictor del desarrollo de un TCA en nuestra población, concordando con lo planteado por sus creadores [17][18][19] , que permite distinguir entre pacientes con anorexia y/o bulimia nerviosa y población normal, pero no distingue anoréxicas de bulímicas.…”
Section: Discussionunclassified
“…Pike et al 6 , informan como desencadenantes de anorexia nerviosa en adolescentes, conflictos y separaciones familiares, cambios de colegio o mudanzas, y aumento en las presiones académicas. La anorexia nerviosa de inicio más tardío, suele antecederse de un mayor número de eventos estresantes, siendo los más importantes conflictos familiares, pérdidas y enfermedades médicas.…”
Section: Rastam Y Gillbergunclassified
See 1 more Smart Citation